Comparative effectiveness of neuroablation and deep brain stimulation for treatment-resistant obsessive-compulsive disorder: a meta-analytic study. Issue 4 (24th January 2019) - Kumar, Kevin K; Appelboom, Geoffrey; Lamsam, Layton; Caplan, Arthur L; Williams, Nolan R; Bhati, Mahendra T; Stein, Sherman C; Halpern, Casey H
Abstract : Background: The safety and efficacy of neuroablation (ABL) and deep brain stimulation (DBS) for treatment refractory obsessive-compulsive disorder (OCD) has not been examined. This study sought to generate a definitive comparative effectiveness model of these therapies. Methods: A EMBASE/PubMed search of English-language, peer-reviewed articles reporting ABL and DBS for OCD was performed in January 2018. Change in quality of life (QOL) was quantified based on the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and the impact of complications on QOL was assessed. Mean response of Y-BOCS was determined using random-effects, inverse-variance weighted meta-analysis of observational data. Findings: Across 56 studies, totalling 681 cases (367 ABL; 314 DBS), ABL exhibited greater overall utility than DBS. Pooled ability to reduce Y-BOCS scores was 50.4% (±22.7%) for ABL and was 40.9% (±13.7%) for DBS. Meta-regression revealed no significant change in per cent improvement in Y-BOCS scores over the length of follow-up for either ABL or DBS. Adverse events occurred in 43.6% (±4.2%) of ABL cases and 64.6% (±4.1%) of DBS cases (p<0.001). Complications reduced ABL utility by 72.6% (±4.0%) and DBS utility by 71.7% (±4.3%). ABL utility (0.189±0.03) was superior to DBS (0.167±0.04) (p<0.001). Interpretation: Overall, ABL utility was greater than DBS, with ABL showing a greater per cent improvement in Y-BOCS than DBS. These findings help guide success thresholds in future clinical trials for treatment refractory OCD.